Enlightenment and lesson from the successful treatment of acute superior mesenteric artery embolism - Wang, Bei; Sun, Rongju; Chen, Wei; Li, Tanshi (Cellular and Molecular Biology, 2017)
Despite recent advances, treatment of acute superior mesenteric artery embolism (SMAE) in emergency is still very difficult. The comparative rarity, the difficulty of early diagnosis, and the extremely high mortality of SMAE give us the sufficient reasons to report our successful experience in curing a patient with acute SMAE. In the present case, the patient was diagnosed early without evidence of intestinal necrosis. The diagnosis of SMAE was verified by computed tomography angiography (CTA). A comprehensive treatment was immediately employed including a combination of intra-arterial thrombolysis and embolectomy operation with emergent laparotomy. We summarize that the successful treatment of superior mesenteric artery embolism depends on early diagnosis and timely reestablishment of arterial flow under the support of general treatments such as prevention of sepsis and control of organic insufficiencies. Through a combined treatment, patient’s life could be saved without complications.